Kinematic changes of the trunk and lower limbs during voluntary lateral sway postural control in adults with low back pain - Chen, Zhengquan; Tirosh, Oren; Han, Jia; Adams, Roger; El-Ansary, Doa; Pranata, Adrian (Frontiers in Bioengineering and Biotechnology, 2024)
Voluntary lateral weight shifting is essential for gait initiation. However, kinematic changes during voluntary lateral weight shifting remain unknown in people with low back pain (LBP). This study aims to explore the differences in kinematics and muscle activation when performing a voluntary lateral weight shifting task between patients with LBP and asymptomatic controls without pain.Methods: Twenty-eight participants volunteered in this study (14 in both the LBP group and the control group). The Sway Discrimination Apparatus (SwayDA) was used to generate a postural sway control task, mimicking lateral weight shifting movements when initiating gait. Kinematic parameters, including range of motion (ROM) and standard deviation of ROM (Std-ROM) of the lumbar spine, pelvis, and lower limb joints, were recorded using a motion capture system during lateral weight shifting. The electroactivity of the trunk and lower limb muscles was measured through surface electromyography using root mean square (RMS). The significant level was 0.05. An independent t-test was employed to compare kinematic parameters, and muscle activation between the LBP group and the control group. A paired-sample t-test, adjusted with Bonferroni correction (significant level of 0.025), was utilized to examine differences between the ipsilateral weight shifting towards side (dominant side) and the contralateral side.The results of kinematic parameters showed significantly decreased ROM and std-ROM of the ipsilateral hip in the transverse plane (tROM=-2.059, p=0.050; tstd-ROM=-2.670, p=0.013), as well as decreased ROM of the ipsilateral knee in the coronal plane (t=-2.148, p=0.042), in the LBP group compared to the control group. For the asymptomatic controls, significantly larger ROM and ROMstd were observed in the hip and knee joints on the ipsilateral side in contrast to the contralateral side (3.287≤t≤4.500, 0.001≤p≤0.006), but no significant differences were found between the two sides in the LBP group. In addition, the LBP group showed significantly lower RMS of the biceps femoris than the control group (tRMS=-2.186, p=0.044).Discussion: Patients with LBP showed a conservative postural control pattern, characterized by reduced ROM of ipsilateral joints and diminished activation of the biceps femoris. These findings suggested the importance of voluntary postural control assessment and intervention to maximize recovery.